Possible application of high-dose vitamin C in the prevention and therapy of coronavirus infection. (December 2020) - Hoang, Ba X.; Shaw, Graeme; Fang, Willian; Han, Bo
Highlights: Viral infections are often associated with increased oxidative stress leading to cellular and tissue damage. Vitamin C has favourable therapeutic properties and a good safety profile in a wide range of clinical applications. High-dose vitamin C has been shown to be a safe and effective therapy for severe cases of respiratory viral infection. Other widely available nutraceuticals can improve the redox balance and reduce tissue damage in viral pneumonia and ARDS. Further clinical trials are needed to validate the effectiveness and to develop an optimal therapeutic protocol. ABSTRACT: Coronaviruses such as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and influenza viruses increase oxidative stress in the body leading to cellular and tissue damage. To combat this, administration of high-dose vitamin C (ascorbic acid or ascorbate), in addition to standard conventional supportive treatments, has been shown to be a safe and effective therapy for severe cases of respiratory viral infection. Morbidity, mortality, infectiveness and spread of infectious diseases are dependent on the host–pathogen relationship. Given the lack of effective and safe antiviral drugs for coronaviruses, there should be more attention in supporting host immune defence, cytoprotection and immunoregulation. Implementation of high-dose vitamin C therapy could dramatically reduce the need for high doses of corticosteroids, antibacterials and antiviral drugs that may be immunosuppressive, adrenal depressive and toxic, complicating the disease course. In order to effectively fight the novel SARS-CoV-2 virus, medical professionals should explore readily available pharmaceutical and nutritional therapeutic agents with proven antioxidant, anti-inflammatory and immunosupportive properties. Supplemental vitamin C may also provide additional benefits for the prevention of viral infections, shorten the disease course and lessen complications of the disease.